Assessor accuracy of the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI): recommendations for reporting items : correspondance - Rupp, Rüdiger (Spinal cord, 2018)
Correspondence
Gesehen am 03.05.2019